Durable clinical benefit of letrozole in leptomeningeal metastasis of breast cancer - Takanashi, Toshihiro (Int Cancer Conf J, 2019)
A case of a woman in her 60s with breast cancer, whose leptomeningeal metastasis (LM) of breast cancer improved remarkably with letrozole monotherapy, is reported. The patient complained of numbness of her left hand and hoarseness, followed by progressive asymmetric extremity weakness and a bladder and rectal disturbance. The patient had undergone surgery for left breast cancer 18 years earlier and was concerned about recurrence of breast cancer, but there were no typical findings with some imaging modalities. The third lumbar puncture showed the malignant cytology of breast cancer, and the patient was diagnosed with recurrent breast cancer. Her performance status was very poor, and it was difficult to administer systemic chemotherapy. Letrozole was started because immunohistochemistry was positive for estrogen and progesterone receptors. After 4 months of letrozole therapy, the symptoms improved gradually. LM has a poor prognosis, and there is little evidence on which to base treatment, but hormone therapy may be an option for LM when the tumor is hormone receptor-positive, slow growing, and has a small volume.